(untitled) (European journal of volunteering and community-based projects, 2023)
This poster provides a structured literature review (SLR) on new emerging technologies supporting the Environmental, Social and Governance aspects (ESG) to identify the interdependencies and relationships between these two areas. Using a rigorous methodological approach, the study summarises the state of the art of the past literature on the topic, which has grown significantly in importance in recent years. The analysis has been conducted on 204 papers extracted from the Scopus database using the Blibliometrix R package. Additionally, using the SLR road, we provide a bibliometric and coding analysis focused on papers published in different academic journals in the business management and accounting field. Our results discover three strands of research: new emissions control technologies, new sustainability assessment management technologies, and disruptive energy management technologies. These results demonstrate the originality of the paper that resides in a novel analysis concerning the recent role played by innovation technologies in sustainability. The study reveals the need for more holistic research and an integrated framework that consider the technological aspects related to ESG criteria, and not consider the two separately as in the present literature. Related to that, there is also the demand for a deeper exploration about the role that new technologies play in the various sustainability initiatives. Finally, the article addresses future research perspectives and paths as joint scholars and practitioners’ analysis.